The effect of carbon dioxide pneumoperitoneum on the healing colonic anastomosis in rats - Durães,Leonardo de Castro (2013)
PURPOSE: To investigate the effects of pneumoperitoneum on colonic anastomosis healing. METHODS: Colonic anastomosis was performed in 120 rats divided into four groups: Group I - pneumoperitoneum before laparotomy, Group II - pneumoperitoneum after laparorrhaphy, Group III - pneumoperitoneum before laparotomy and after laparorrhaphy, Group IV - no pneumoperitoneum (control group). Pneumoperitoneum pressure was 5 mmHg. Animals were killed on the 3rd, 7th and 14th postoperative day. Hhistopathological features, anastomosis breaking strength, collagen histomorphometry and hydroxyproline concentration were assessed. RESULTS: Breaking strength between groups: (day 3, p=0.165; day 7, p=0.219; day 14, p=0.539). Histopathology revealed that group II had, on day 7, less infiltration of mononuclear cells (p=0.006), greater infiltration of polymorphonuclear cells (p=0.001) and greater necrosis (p=0.001); and on day 14, less fibrosis. Histomorphometry revealed a decrease in collagen in groups I and III (p<0.001) on day 7 and an increase in groups I and II on day 14 (p<0.001). Hydroxyproline concentration was similar for groups on days 3 (p=0.152), 7 (p=0.913) or 14 (p=0.981). CONCLUSION: Carbon dioxide does not impair the healing of colonic anastomosis in rats.